Evaluation of the ecotoxicological effects of biogenic amines derived from cadaverous putrefaction on springtails Folsomia candida - Braga, Ana Paula Andrade [UNESP]; Gonçalves, Matheus de Moraes Cunha [UNESP]; de Souza, Cleiton Pereira [UNESP]; Marin-Morales, Maria Aparecida [UNESP] (Springer Nature, 2023)
Necro-leachate, a liquid released during cadaveric decomposition, is considered the main culprit for impacts on cemetery environments. The biogenic amines cadaverine and putrescine make up part of the composition of necro-leachate and have a certain toxicity to different organisms. Springtails are among the most used bioindicators to assess the impacts of soil contaminants. As there are no data on the acute and chronic toxicity of springtails exposed to cadaverine and putrescine, the objective of this study was to evaluate the toxic potential of both amines, under the behavioral effect of avoidance and reproduction in the species Folsomia candida. Springtails were exposed to soils contaminated with different concentrations of cadaverine and putrescine, and different mixtures of these amines. To evaluate the avoidance and reproduction test, the individuals were exposed for periods of 48 h and 28 days, respectively. The results obtained in the avoidance test showed that springtails exhibited a preference for the treated soil in both isolated and mixed treatments. The chronic evaluation assays showed that the reproduction was affected, particularly in the treatments with combined amines, resulting in a reduction in the total number of juveniles. From the results, it is possible to infer that the methods applied in this research have provided information that will contribute to a better understanding of the toxicity of putrefactive biogenic amines, since there exist few ecotoxicological studies carried out with these amines, and especially with those from cemetery environments.
Keywords: Avoidance test; Cadaverine; Cemeteries; Necro-leachate; Putrescine; Reproduction test